TRPV4—A Multifunctional Cellular Sensor Protein with Therapeutic Potential - Sanna Koskimäki; Sari Tojkander (Sensors, 2024)
Transient receptor potential vanilloid (TRPV) channel proteins belong to the superfamily of TRP proteins that form cationic channels in the animal cell membranes. These proteins have various subtype-specific functions, serving, for example, as sensors for pain, pressure, pH, and mechanical extracellular stimuli. The sensing of extracellular cues by TRPV4 triggers Ca2+-influx through the channel, subsequently coordinating numerous intracellular signaling cascades in a spatio-temporal manner. As TRPV channels play such a wide role in various cellular and physiological functions, loss or impaired TRPV protein activity naturally contributes to many pathophysiological processes. This review concentrates on the known functions of TRPV4 sensor proteins and their potential as a therapeutic target.